Integrin alpha-5 silencing leads to myofibroblastic differentiation in IPF-derived human lung fibroblasts - Gali Epstein Shochet; Elizabetha Brook; Becky Bardenstein-Wald; Hanna Grobe; Evgeny Edelstein; Lilach Israeli-Shani; David Shitrit (SAGE Publishing, 2020)
Background and objective: The term 'fibroblast' covers a heterogeneous cell population in idiopathic pulmonary fibrosis (IPF). The fibroblasts are considered as main effector cells, because they promote disease progression by releasing exaggerated amounts of extracellular matrix proteins and modifying cell microenvironment. As IPF-derived human lung fibroblasts (IPF-HLFs) were shown to express higher levels of integrin alpha-5 (ITGA5) than normal derived HLFs (N-HLFs), we explored the importance of ITGA5 to IPF progression. Methods: IPF-HLF and N-HLF primary cultures were established. ITGA5 was silenced by specific small interfering RNA (siRNA)s and its effects on cell phenotype (e.g. cell number, size, cell death, migration) and gene expression (e.g. RNA sequencing, quantitative polymerase chain reaction [qPCR], western blot and immunofluorescence) were tested. Specific integrin expression was evaluated in IPF patient formalin-fixed paraffin embedded sections by immunohistochemistry (IHC). Results: ITGA5-silencing resulted in reduced IPF-HLF proliferation rates and cell migration ( p  < 0.05), as well as elevated cell death. transforming growth factor beta (TGF-β) targets (e.g. Fibronectin (FN1), Matrix metalloproteinase 2 (MMP2), TGFB1) were surprisingly elevated following ITGA5 silencing ( p  < 0.05). N-HLFs, however, were only slightly affected. Interestingly, ITGA5-silenced cells differentiated into myofibroblasts (e.g. elevated alpha-smooth muscle actin [αSMA], collagen1a, large cell size). RNA-sequencing revealed that following differentiation on 3D-Matrigel for 24 h, ITGA5 levels are reduced while integrin alpha-8 (ITGA8) are elevated in IPF-HLFs. This was confirmed in IPF patients, in which ITGA5 was mainly found in fibroblastic foci, while ITGA8 was mostly observed in old fibrous tissue in the same patient. Conclusions: ITGA5 expression facilitates a more aggressive proliferative phenotype. Downregulation of this integrin results in myofibroblastic differentiation, which is accompanied by elevated ITGA8. Specific targeting could present a therapeutic benefit.